2018
DOI: 10.7717/peerj.5628
|View full text |Cite
|
Sign up to set email alerts
|

Different environmental gradients affect different measures of snake β-diversity in the Amazon rainforests

Abstract: Mechanisms generating and maintaining biodiversity at regional scales may be evaluated by quantifying β-diversity along environmental gradients. Differences in assemblages result in biotic complementarities and redundancies among sites, which may be quantified through multi-dimensional approaches incorporating taxonomic β-diversity (TBD), functional β-diversity (FBD) and phylogenetic β-diversity (PBD). Here we test the hypothesis that snake TBD, FBD and PBD are influenced by environmental gradients, independen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 83 publications
1
7
0
Order By: Relevance
“…Additionally, we used the phylosor (1‐phylosor) function of the picante R ‐package to estimate phylogenetic distances based on fractions of branch‐length shared among paired modules. By applying a simple linear regression given by functional distance = a + b (phylogenetic distance) , we found a positive relationship ( r 2 = 0.40, p < 0.00001), which indicates that functional distance is a good proxy for phylogenetic distance in our study system, consistent with snake assemblages in Amazonia (Fraga et al, 2018).…”
Section: Methodssupporting
confidence: 84%
See 2 more Smart Citations
“…Additionally, we used the phylosor (1‐phylosor) function of the picante R ‐package to estimate phylogenetic distances based on fractions of branch‐length shared among paired modules. By applying a simple linear regression given by functional distance = a + b (phylogenetic distance) , we found a positive relationship ( r 2 = 0.40, p < 0.00001), which indicates that functional distance is a good proxy for phylogenetic distance in our study system, consistent with snake assemblages in Amazonia (Fraga et al, 2018).…”
Section: Methodssupporting
confidence: 84%
“…Many studies have shown turnover of species assemblages in Amazonia (e.g. Fraga et al, 2018; Rojas‐Ahumada et al, 2012), but the scale of those studies was too limited to detect neutral effects due to dispersal limitation. To increase the geographical coverage in an area with no obvious dispersal barriers, a multidisciplinary effort has been applied to provide an efficient sampling design to quantify dissimilarities among assemblages based on standardized sampling plots installed along the Madeira‐Purus interfluvial region, in the Midwestern Amazonia (PPBio, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Shelford's law, a single factor has an effect when it is at the minimum or maximum of that species' tolerance zone (Shelford, 1911(Shelford, , 1931. In most cases, species do not respond to individual environmental factors, but to complex gradients of different environmental factors (Rydgren et al, 2003;de Fraga et al, 2018). Ecoclines, which can be represented by the DCA ordination axes, are considered as the markers of complex ecological gradients (Rydgren et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In general, it is expected that habitat-specialist species find inadequate-to-optimum continuums of environmental conditions for survival and reproduction [34]. Environmental filtering has been found in Amazonia for plants, frogs, lizards, snakes, and birds [15,[35][36][37][38][39][40][41][42][43]. For lizards, local assemblages may differ due to variation in individual abundance or species turnover along gradients of distance from water courses [31,44], elevation [45], climate seasonality [46], and number of trees [43,47].…”
Section: Introductionmentioning
confidence: 99%